Advancing the Financial Inclusion with Profit Sharing Scheme for the Sustainability of Indonesian MSMEs - Saratian, Eko Tama Putra; Arief, Harefan; Oktaviar, Chairiel; Marlapa, Eri; Soelton, Mochamad (Indonesian Journal of Society Development, 2024)
This community service is related to economic society development by introducing financial inclusion with the profit-sharing financing scheme for the sustainability of The Indonesian Micro, Small, and Medium Enterprises (MSMEs). The partner of this community service is Pondok Aren District, in this case, the Cooperatives & UMKM Service, South Tangerang, Banten 15228. Pondok Aren District is multiplying, with a population of around 294,996. This is directly proportional to the number of MSMEs reported based on the SKDU document, which is around 1,373. Currently, the government, through the Financial Services Authority (OJK), is calling on the public to continue to encourage the progress of the Sharia Financial Industry, which has grown rapidly in the last five years both. For this reason, there is a need for an advancement in understanding Sharia profit-sharing financing and literacy about Sharia financing products that can be implemented for the MSMEs